The Effect of Leadership and Motivation on Employee Performance at PT Bumi Rajawali in Tangerang - Rozi, Achmad (Program Pascasarjana Universitas Negeri Makassar, 2020)
This study aims to determine the effect of leadership and motivation on employee performance at PT. Bumi Rajawali in Tangerang. The method used was explanatory research with a sample of 90 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study leadership has a significant effect on employee performance by 36.2%, hypothesis testing obtained significance 0,000 <0.05. Motivation has a significant effect on employee performance by 45.3%, hypothesis testing obtained significance 0,000 <0.05. Leadership and motivation simultaneously have a significant effect on employee performance by 52.1%, hypothesis testing obtained significance of 0,000 <0.05.